Measuring macroeconomic tail risk - Marfè, Roberto; Pénasse, Julien (Journal of Financial Economics, 2024)
This paper estimates consumption and GDP tail risk dynamics over the long run (1900–2020). Our predictive approach circumvents the scarcity of large macroeconomic crises by exploiting a rich information set covering 42 countries. This flexible approach does not require asset price information and can thus serve as a benchmark to evaluate the empirical validity of rare disaster models. Our estimates covary with asset prices and forecast future stock returns, in line with theory. A calibration disciplined by our estimates supports the prediction that macroeconomic tail risk drives the equity premium.